Restructuring Palm Oil's Fat Structure to Replace Butter: Assessing Physicochemical, Composition, and Rheology Changes in Dark, Milk, and White Chocolate Ganache (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Ganache is made from a combination of chocolate and dairy cream. Dark, milk, and white chocolate compounds can be used to make ganache, in which some of the cocoa butter is replaced with other vegetable fats in the compound chocolate. Palm oil is used as an alternative to butter due to its availability and can help lower the cost of production of confectionery products. Chocolate ganache is prepared with chocolate compound, whipped cream, RBD palm oil, unsalted butter, and inverted sugar, then mixed on a hot plate. This study added 70% and 100% RBD palm oil to the dark, milk, and white chocolate ganache as a substitution for butter. The effect of RBD palm oil on the physicochemical properties of the ganache was evaluated. Several analyses have been done, including pH, moisture content, water activity, colour profile, texture profile, viscosity, and fat analyses. Dark, milk, and white chocolate ganache made with unsalted butter were used as control samples. The addition of RBD palm oil did not significantly affect the pH, moisture content, water activity, and colour of chocolate ganache. This study showed that the dark chocolate ganache with RBD palm oil has the highest viscosity than other samples. It suggests that dark, milk, and white chocolate ganache with 100% RBD palm oil are the preferred formulations due to their viscosity. These three preferred formulations showed the highest percentage of fatty acid at C12:0, C14:0, C16:0, and C18:0. The main distribution of triacylglycerol for these three formulations is on C50 and C52.
Keywords: Alternative fats; Chocolate compound; Cocoa; Confectionery; Emulsion